A tradução do guia turístico : a convencionalidade e as marcas do tradutor - Santana, Evandro (2014)
One of the objectives of the activity of translation is to make a certain text available to those who speak a language different from the one in which the original text was produced. So as to achieve the purpose of the translation task, it is essential that the translator give specific attention to issues related to text production. Text genre is, for instance, important, since the choices made by the translator are oriented by the understanding of the socio-communicative goals of the translated text. Among the problems that can be observed in translation, one notices that the non-use of appropriate lexical phrases and the misuse of words and expressions in certain contexts, reveal an inadequate use of conventionality. This misuse of expressions and words are often indications that show, or even prove, that the text is translated. In this study, our intention is to investigate the signs left by the translator. To do so, we rely on estereoscopic readings (which consist of studying parallel texts) to analyse translations performed by a group of student- translators. Three texts are available for analysis: an original text in Portuguese, a first version of the original text translated to English and the final version, that is, its reviewed version in English. The choice and use of vocabulary and lexical phrases are also analyzed by applying the theory of relevance, so as to verify the appropriateness of the translator"s choices. The analysis demonstrates that most language items which indicate that the text was translated, those inadequate choices and selection of language observed in the material studied, mainly those identified in the first draft of the text translated into English, are due to the fact that they do not conform to the conventionality of the English language, but reproduce that of the source language.